2015
DOI: 10.3390/e17064454
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Soil Moisture Profiles in Irrigated Fields by the Principle of Maximum Entropy

Abstract: Vertical soil moisture profiles based on the principle of maximum entropy (POME) were validated using field and model data and applied to guide an irrigation cycle over a maize field in north central Alabama (USA). The results demonstrate that a simple two-constraint entropy model under the assumption of a uniform initial soil moisture distribution can simulate most soil moisture profiles that occur in the particular soil and climate regime that prevails in the study area. The results of the irrigation simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…As a first test case, SCAN site number 2078 in Madison, Alabama, which was also used in Mishra et al [43] was considered. Mishra et al [43] found the SCAN data to provide ideal test cases for evaluating fitting capabilities of their proposed SMP model. They indicated that two general shapes of soil moisture profiles are commonly observed in course of the drying process: (i) the "dynamic case", which is analogous to earlier times of drying shown in Figure 1; and (ii) the "dry case", which is similar to the late drying times in Figure 1.…”
Section: Measured Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As a first test case, SCAN site number 2078 in Madison, Alabama, which was also used in Mishra et al [43] was considered. Mishra et al [43] found the SCAN data to provide ideal test cases for evaluating fitting capabilities of their proposed SMP model. They indicated that two general shapes of soil moisture profiles are commonly observed in course of the drying process: (i) the "dynamic case", which is analogous to earlier times of drying shown in Figure 1; and (ii) the "dry case", which is similar to the late drying times in Figure 1.…”
Section: Measured Datamentioning
confidence: 99%
“…As a first test case, SCAN site number 2078 in Madison, Alabama, which was also used in Mishra et al [43] was considered. Mishra et al [43] found the SCAN data to provide ideal test cases for evaluating fitting capabilities of their proposed SMP model.…”
Section: Measured Datamentioning
confidence: 99%
“…Some infiltration equations were derived based on the principle of maximum entropy (PME) with the Shannon entropy or information entropy [9] as well as soil moisture movement on the basis of PME with Tsallis entropy [10]. The soil moisture distribution was also estimated in an irrigated field in North Central Alabama, USA, based on the PME [11]. These studies assumed that the vertical soil moisture distribution curve is a scaled probability density function (PDF) that follows PME.…”
Section: Introductionmentioning
confidence: 99%
“…(4). In fact, it is clear that some profiles can be parabolic in shape (i.e., demonstrate an inflection point), especially immediately subsequent to rain events (dynamic case), or due to sharp changes in soil characteristics (Al-Hamdan and Cruise, 2010;Mishra et al, 2015). These cases are identified when mass balance cannot be kept by the monotonic assumption and thus Eq.…”
mentioning
confidence: 99%
“…(4) has no solution. In these cases, it is 290 assumed that the inflection point is located in the soil layer with the greatest field capacity (Mishra et al, 2015). The POME model is then applied twice; from the surface to the inflection point, and then from the inflection point to the bottom boundary.…”
mentioning
confidence: 99%